A Comparative Study of Ibn Arabi and Al-Hallaj on Spirituality and Mysticism in Islamic Sufism - Toat Haryanto; Enjang (Masagi: Jurnal Pendidikan Karakter, 2025)
This study explores spirituality and mysticism in Islamic Sufism by examining the thoughts of two prominent figures, Ibn Arabi and Al-Hallaj. Both are known for their major contributions to the Sufi tradition, yet they present distinct approaches in understanding the relationship between humans and God. The study arises from the limited number of comparative analyses concerning the spiritual and mystical perspectives of these two thinkers. The aim is to identify similarities and differences in their mystical concepts and to reveal the richness of spiritual expression within Sufism. This research employs a qualitative library method, analyzing primary works such as Ibn Arabi’s al-Futūḥāt al-Makkiyya and Fuṣūṣ al-Ḥikam, and Al-Hallaj’s Ṭawāsīn, along with supporting secondary literature. Data collection was conducted through documentation, involving classification and interpretation of both primary and secondary sources. Data were analyzed using content and hermeneutical approaches to interpret textual meanings in their historical, philosophical, and spiritual contexts. The findings show that Ibn Arabi emphasizes a metaphysical and rational dimension through the concept of Wahdat Al-Wujūd, while Al-Hallaj focuses on ecstatic experience and divine love. Both perspectives enrich the understanding of spirituality in Islam, demonstrating the diversity of expressions in seeking closeness to God. This study contributes to Sufi scholarship by deepening appreciation of the plurality of spiritual paths and the interrelation between metaphysical thought and inner experience.